Epidemiologic Monitoring of Enterovirus (Nepolio) Infection: Rationale for Improvement - M. V. Novoselova; E. V. Albaut; E. B. Brusina (Эпидемиология и вакцинопрофилактика)
Relevance. Non-polio enteroviruses are widespread worldwide, with millions of cases being reported each year, but limited data exist on the true burden of enterovirus (non-polio) infections (EVnI) worldwide due to a lack of standardized surveillance. Considering the absence of specific prevention of EnVI and the difficulty of predicting the epidemic situation due to the diversity of types of enteroviruses, there is an obvious need for substantiating and supplementing the existing parameters of epidemiological monitoring, identifying additional indicators of morbidity risk for the purpose of timely implementing preventive and anti-epidemic measures. Aim. Rationale of necessity of additional measures of the EVnI observation for early discovery of the activation of the epidemic process. Materials and methods. The research was held during the year 2023 and included the following three components: 1. The prospective continuous observation of the patients ranging from 0 to 18 years old who received medical help in ambulatory conditions. Possible symptoms of EVnI were studied using the ambulatory diseased person’s medical cards (f. № 0/25у). 2. The research of biological material, which belonged to the healthy people and people with signs of probable EVnI. 3. The study of epidemiological connection of dew point temperature with the manifestations of the EVnI epidemic process. Results. Probable clinical symptoms of EVnI are found among 511 observed children. Positive correlational connection with EVnI is visible among exanthems (0,43, p < 0,001) and acute nasopharyngitis (0,13, p < 0,001). The maximal incidence rate of EVnI is discovered in a period from 27th to 36th week (54,35 ‰), which coincides with maximal incidence rate of acute nasopharyngitis (434,78 ‰). The rise in incidence rate of EVnI in comparison to the last period is 4,45 times (p < 0,001), while in comparison to the rise in incidence rate of acute nasopharyngitis is 2,71 times (p < 0,0001). In planned observation of examined patients with probable symptoms, EVnI disease is found amongst 78 people, the incidence rate made 254,07 ‰ and that aligns with the results of active observation of health center appeals (267,68 ‰, p > 0,99). Clinical diagnosis of EVnI is made only in 51,28 %% of all cases. As a result of ill and healthy people’s observation, their relation is found to be 6:1 respectively. The activation of the epidemic process started in concurrence with dew point temperature +4,85 °C and continued until the dew point temperature +20,33 °C. Conclusion. The existing system of epidemiological supervision over EVnI has to be enhanced by adding the research on NPEV among the people who have acute nasopharyngitis during the stable rise in dew point temperature from +5,0 °C. Taking into account the rise in the incidence rate of EVnI, it is reasonable to expand the microbiological observation of biological material which belongs to the people who have exanthems, diarrheal syndrome and healthy people